The Use of Artificial Intelligence Tools in Assessing English Writing Accuracy - Norpoʻlatova Nozima Yusufxon qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores the use of artificial intelligence (AI) tools in assessing English writing accuracy among EFL learners. With the rapid advancement of AI technology, educational applications such as automated writing evaluation (AWE) systems have become increasingly popular. These tools provide immediate feedback on grammar, vocabulary, punctuation, and overall writing coherence. The study examines the benefits and limitations of AI-based assessment, focusing on its role in enhancing learner autonomy, improving writing accuracy, and supporting teachers in large classrooms. Evidence from recent research and classroom applications indicates that AI tools can significantly improve feedback efficiency, promote self-correction, and help learners develop linguistic precision, though human oversight remains crucial for assessing creativity, context, and discourse-level quality.